THE DYNAMICS OF THE MEANING OF BELIS IN THE MARRIAGE TRADITION OF SUMBA PEOPLE IN WEEPATANDO VILLAGE - I Made Sila; I Nengah Sudiarta; Maria Goreti Amurni (International Journal of Education and Social Science Studies, 2024)
Marriage adopted in Sumba society is an effort to maintain offspring that takes place according to the patrilineal kinship system. The problem in this study is related to the form of panai money in the tradition of marriage in Weepatando village, Wewewa sub-district, southwest Sumba district.  An indicator of informants using an impressive sampling technique, with informants numbering six. Data gathering techniques using interview techniques. The analysis techniques used in this research are qualitative data in analysis. This research uses qualitative research methods by conducting interviews, observation, and documentation in the research. The research location is located in Wewewa sub-district, southwest central Sumba district. The results of this study show that the Wewewa community still preserves the traditional marriage ceremony by asking for a large belis. However, the meaning of belis in the district has changed drastically. Through this research, the philosophical meaning of belis can be revealed, which is actually used as a means of tying mystical ropes between two families or between clans.